Peak myocardial work index: a novel nonproprietary approach for the assessment of global constructive myocardial work by strain echocardiography - Chen, Peng; Kiriakou, Christina; Aurich, Matthias; Greiner, Sebastian; Maliandi, Gabriele; Müller-Hennessen, Matthias; Giannitsis, Evangelos; Meder, Benjamin; Frey, Norbert; Pleger, Sven Torsten; Mereles, Derliz (The international journal of cardiovascular imaging, 2025)
Myocardial work indices (MW) have been validated with respect to their efficiency for predicting cardiac events in patients with heart failure. However, the measurement of MW requires specific vendor software that may not be ubiquitous accessible. We aimed to explore the feasibility of using a nonproprietary method, peak myocardial work index (PMW) = systolic blood pressure * global longitudinal strain, as a potential substitute to global constructive work (GCW) for the assessment of left ventricular function. A retrospective analysis of 116 patients with dilated cardiomyopathy (DCM) and an equal number of age- and sex-matched healthy controls examined from June 2009 to July 2014 was conducted. Compared to healthy controls, the PMW index and GCW were significantly lower in DCM patients: 1371 ± 541 vs. 2520 ± 361 mm Hg%, 1318 ± 502 vs. 2322 ± 333 mm Hg%, respectively (p < 0.001 for each). Additionally, PMW showed an excellent correlation with GCW (r = 0.99, p < 0.001). During a mean follow-up time of 5.1 years, 34 patients (29.3%) reached the composite endpoints: 5 patients received cardiac transplantation, 17 patients were hospitalized due to heart failure, 9 patients received appropriate ICD therapy and 3 patients died. PMW per 50 mm Hg% increase (HR = 0.92, 95%CI 0.89-0.96, p < 0.001) and GCW per 50 mm Hg% increase (HR = 0.91, 95%CI 0.88-0.95, p < 0.001) performed comparably in predicting adverse outcomes in DCM patients in the univariate Cox regression analyses. PMW and GCW were the independent prognostic factors after adjusting for significant parameters of the univariate analysis. Patients with PMW < 1,286 mm Hg% (HR = 3.71, 95%CI 1.18-11.63, p = 0.025) and GCW < 1,238 mm Hg% (HR = 4.8, 95%CI 1.57-14.68, p = 0.006) had higher risks of MACE. PMW index might serve as an alternative echocardiographic method for evaluating left ventricular systolic function, providing similar diagnostic and prognostic capacity comparable to GCW.
Online veröffentlicht am 26. September 2026
Gesehen am 16.01.2026